Plant host and drought shape the root associated fungal microbiota in rice - Andreo-Jimenez, Beatriz; Vandenkoornhuyse, Philippe; Lê Van, Amandine; Heutinck, Arvid; Duhamel, Marie; Kadam, Niteen; Jagadish, Krishna; Ruyter-Spira, Carolien; Bouwmeester, Harro (PeerJ, 2019)
and Aim Water is an increasingly scarce resource while some crops, such as paddy rice, require large amounts of water to maintain grain production. A better understanding of rice drought adaptation and tolerance mechanisms could help to reduce this problem. There is evidence of a possible role of root-associated fungi in drought adaptation. Here, we analyzed the endospheric fungal microbiota composition in rice and its relation to plant genotype and drought. Methods Fifteen rice genotypes (Oryza sativa ssp. indica) were grown in the field, under well-watered conditions or exposed to a drought period during flowering. The effect of genotype and treatment on the root fungal microbiota composition was analyzed by 18S ribosomal DNA high throughput sequencing. Grain yield was determined after plant maturation. Results There was a host genotype effect on the fungal community composition. Drought altered the composition of the root-associated fungal community and increased fungal biodiversity. The majority of OTUs identified belonged to the Pezizomycotina subphylum and 37 of these significantly correlated with a higher plant yield under drought, one of them being assigned to Arthrinium phaeospermum. Conclusion This study shows that both plant genotype and drought affect the root-associated fungal community in rice and that some fungi correlate with improved drought tolerance. This work opens new opportunities for basic research on the understanding of how the host affects microbiota recruitment as well as the possible use of specific fungi to improve drought tolerance in rice.